Alpha modulation during working memory encoding predicts neurocognitive impairment in ADHD. (18th March 2019) - Lenartowicz, Agatha; Truong, Holly; Salgari, Giulia C.; Bilder, Robert M.; McGough, James; McCracken, James T.; Loo, Sandra K.
Abstract : Background: Attention‐deficit/hyperactivity disorder (ADHD) is associated with working memory (WM) deficits. However, WM is a multiprocess construct that can be impaired through several pathways, leaving the source of WM impairments in ADHD unresolved. In this study, we aim to replicate, in an independent sample, previously reported deficits in component processes of WM deficits in ADHD and expand to consider their implications for neurocognitive outcomes. Methods: In 119 children (7–14 years old, 85 with ADHD), we used electroencephalography measures to quantify component processes during performance of a spatial working memory task. We quantified stimulus encoding using alpha range (8–12 Hz) power; vigilance by the P2 event‐related potential to cues; and WM maintenance by occipital‐alpha and frontal‐theta (4–7 Hz) power. These measures were evaluated against metrics of executive function, ADHD symptoms, and academic achievement. Results: Encoding alpha‐power decreases and cue P2 amplitude were attenuated in ADHD, whereas occipital‐alpha power during maintenance was significantly greater in ADHD, consistent with a compensatory response to weak encoding. Weak alpha modulation during encoding was associated with poorer reading comprehension and executive function, as well as enhanced ADHD symptoms. Previously reported effects in frontal‐theta power failed to replicate. Conclusions: Stimulus encoding, a component process of WM coupled to alpha modulation, is impaired in ADHD, and, unlike WM maintenance or vigilance processes, has implications outside of the laboratory via a relationship with executive function, and, to a weaker extent, reading comprehension.